RETURN MIGRATION TO THE BRAZILIAN SEMI-ARID NORTHERN REGION - Gomes de Oliveira, Herick Cidarta; Costa, Jose Vilton; Ojima, Ricardo (Mercator, 2019)
In a strict sense, the migrant to return is understood by the individual who left their region of birth, he resided for some time in a different region and with certain time returns to its place of origin. In this context, the objective of this study was to analyze the process of return migration in the municipalities of the northern brazilian semiarid (SemiSet), between the periods 1995/2000 and 2005/2010 and estimate the return flows in the region. This region is composed by 755 municipalities, located above the São Francisco river, in the states of Rio Grande do Norte, Ceará, Paraíba, Pernambuco, Alagoas and Piauí. We used the Demographic Censuses of 2000 and 2010, which adopted the criterion "fixed date" for definition of the returnees. It has been observed that in relation to the region of origin (former residence) of returnees, in the period 1995/2000 predominated the return of individuals from the Southeastern region of the country. In the period 2005/2010, reverses the position between the Southeast and Northeast, with a reduction of 29% of those who came from the East and an increase of 48% between the returned from the own Northeast. Keywords : migration; return migration; semiarid northern.